Importance Modulates the Temporal Features of Self-Referential Processing: An Event-Related Potential Study - Xu, Kepeng; Li, Shifeng; Ren, Deyun; Xia, Ruixue; Xue, Hong; Zhou, Aibao; Xu, Yan (Frontiers in Human Neuroscience, 2017)
A growing number of studies have demonstrated preferential processing of self-related information. However, previous research has been limited in examining the distinction between processes related to the self and those related to the non-self, it remains unclear how self-related information with differing levels of importance is processed within the self. The present study examined how the importance of self-related content affects the neural activity involved in self-referential processing. The behavioral results showed that the participants had faster responses to more important self-related content. The event-related potential results showed that early attention resources were diverted to the identification of highly important self-related content compared with minimally important self-related content, as reflected by the enhanced P200. Furthermore, the N200 amplitude for highly important self-related content was smaller than for moderately important self-related content which, in turn, were smaller than minimally important self-related content. Moreover, the P300 amplitudes were modulated by the degree of importance of self-related content, whereby a higher importance of self-related content led to larger P300 amplitudes. Taken together, these findings demonstrate an effect of the degree of importance of the self-related content at both behavioral and neurophysiologic levels.